2005
DOI: 10.1002/ijc.21510
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the stress-related MHC class I chain-related protein MICA is an indicator of good prognosis in colorectal cancer patients

Abstract: The realization of targeted cancer therapy has driven the need to improve selection of patients with colorectal cancer for adjuvant therapy, leading to a search for potential new prognostic markers. There is accumulating evidence that immunosurveillance acts as an extrinsic tumor suppressor. As genetic instability is an early event in colorectal cancer, this can lead to altered expression of molecules conferring resistance to immune attack. Hence, molecules up or downregulated in this process may impact on pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
91
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 27 publications
(28 reference statements)
11
91
2
1
Order By: Relevance
“…As previously shown, MICA/B protein was detected with different subcellular localization patterns (mainly cytoplasmic) in 58% of samples (Fig. 8A, Table I) (30). A polarized abluminal staining was observed in 71% of well-differentiated tumors, whereas it was not detected in poorly differentiated tumors (Fig.…”
Section: Mica/b Expression Is Lost and Infiltration Of Nkg2d + Lymphosupporting
confidence: 70%
“…As previously shown, MICA/B protein was detected with different subcellular localization patterns (mainly cytoplasmic) in 58% of samples (Fig. 8A, Table I) (30). A polarized abluminal staining was observed in 71% of well-differentiated tumors, whereas it was not detected in poorly differentiated tumors (Fig.…”
Section: Mica/b Expression Is Lost and Infiltration Of Nkg2d + Lymphosupporting
confidence: 70%
“…4,5 NKG2DL, however, are stress-inducible and often found to be expressed on a variety of solid tumors and lymphoproliferative malignancies. [6][7][8][9][10][11][12][13][14][15] Consequently, the expression of both, the NKG2D receptor and its ligands, has a crucial role in immune defense mechanisms against tumor cells by T and NK cells: studies in mice showed that NK and CD8 T cells eliminated NKG2DL-positive tumor cells through the NKG2D receptor. 16,17 It was further shown that NKG2D protected the host from tumor initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of the expression of MIC genes in response to biological stress is recognized by the NKG2D activating receptors in NK cells, ab T and cd T lymphocytes acting as a mechanism of immunosurveillance [17][18][19]. Engagement of NKG2D by MIC costimulates antigenspecific cytolytic and cytokine responses in CD8ab T cells under suboptimal TCR stimulation conditions, such as the down-modulation of MHC-I frequently associated with tumors but NKG2D alone can also trigger cd T and NK cells in a TCR-independent manner [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%